Microbial aetiology and diagnostic criteria of postpartum endometritis in Nairobi, Kenya. Issue 3 (June 1988) - Temmerman, M; Laga, M; Ndinya-Achola, J O; Paraskevas, M; Brunham, R C; Plummer, F A; Piot, P
Abstract : Using a protected triple lumen device, Neisseria gonorrhoeae or Chlamydia trachomatis, or both, were isolated from the endometriums of five out of 35 women with clinical postpartum endometritis compared with none of a control group of 30 puerperal women without endometritis (p less than 0.05) in Nairobi, Kenya. These sexually transmitted agents were also found in 12 cervical specimens from women with and three without postpartum endometritis (p = 0.04). Mycoplasma hominis and Ureaplasma urealyticum were equally isolated from the endometrium in both groups. Histology showed plasma cell infiltration in 6/25 patients compared with 1/22 controls (p = 0.06). A history of foul lochia (p less than 0.01) and abdominal pain (p = 0.02) were associated with postpartum endometritis. Sexually transmitted agents appear to be major causes of puerperal upper genital tract infections in Nairobi.